Yellowknife, NT -- photograph - Seale, Linda N. (2011)
View west from Pilots' Monument in Old Town, Yellowknife, NT, to the new town area, high rises and Yellowknife Bay. The tower to the left with a red top is the Con Mine tower or Robertson Headframe at the disused Cominco gold mine (demolished October 29 2016). The tower was a prominent landmark for hikers and boaters, and was visible from aircraft landing in Yellowknife. The road is Franklin Avenue. Photograph taken January 2011: description updated October 2016